Assessment of Quality of Educational Result in Institutions the General and Professional Education of the Leningrad Region - Anatoly Vladimirovich Kluev; Svetlana Vsevolodovna Lyashko; Sergey Valentinovich Tarasov (Управленческое консультирование)
As a result of sociological research are identified major trends occurring in the educational process of general secondary education in institutions of the Leningrad region. Also the attitude of students to the educational process and the level of basic skills are measured. The study used a cognitive and axiological approach that will determine the quality indicators and may impact the educational process.